DAMPAK PENGGUNAAN INSTAGRAM TERHADAP ETIKA KEWARGANEGARAAN DI INDONESIA - Juliani, Aisya; Sulistyarini, Sulistyarini; Dewantara, Jagad Aditya (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2025)
The rapid growth of Instagram as a social media platform has significantly influenced social interactions, particularly among young people in Indonesia. While it serves as a space for self-expression, learning, and digital activism, its impact on civic ethics remains a critical concern. This study aims to analyse the influence of Instagram usage on civic ethics among Indonesian youth. Employing a mixedmethods approach, the research integrates quantitative data from a survey of 300 respondents aged 17 to 30 across five major cities"”Jakarta, Surabaya, Bandung, Medan, and Makassar"”and qualitative data from in-depth interviews with 15 informants including academics, social media activists, and active Instagram users. The findings reveal a dual impact: on the positive side, Instagram fosters civic awareness and digital participation; on the negative side, it facilitates the spread of misinformation, digital intolerance, and emotional reactions to social issues. The thematic analysis further indicates that digital literacy significantly affects the quality of civic behavior on social platforms. The study concludes that while Instagram can promote civic engagement, its positive outcomes depend on users"™ critical thinking and ethical conduct. Therefore, digital literacy education and regulatory frameworks are essential to strengthen civic values in the digital public sphere.